Покарання військових в античних державах - Логвиненко, Є. С.; Lohvynenko, Ye. S.; Логвиненко (Велика) Євгенія Сергіївна (Право і безпека. – 2017. – № 1 (64). – С. 31-35, 2017)
Показано, що полісний тип державності обумовлював формування в кожному місті-державі своєї самостійної правової системи. З’ясовано, що спільної уніфікованої системи покарань військових у Давній Греції не існувало. Проте афінське право було більш юридично розвинутим з усіх правових систем полісів і впливало на формування правових інститутів інших античних міст-держав. Показано, як кримінальне право Афін достатньо чітко визначало військові покарання за найбільш небезпечні та тяжкі за своїми наслідками злочини. Розглянуто також ставлення до військовополонених, види та способи їх покарання. Показано також, що у Давньому Римі, на відміну від Давньої Греції, склалася доволі диференційована система видів військових злочинів та покарань, націлена на встановлення жорсткої дисципліни в армії.

It has been demonstrated that the polis type of statehood conditioned the formation of the independent legal system in each city-state. It was found out that there was no common uniform system of servicemen punishment in the Ancient Greece. However, the Athenian law was more developed comparing to legal systems of other ancient city-states. The author has studied the criminal law of Athens, which clearly, unlike other policies, determined the punishment of servicemen for the most dangerous and severe in its consequences crimes. The death penalty or expulsion – that was the verdict for crimes against the polis, which were considered antisocial and anti-state. These included evasion of paying military tax and breach of military duty. It has been established that the murder was more legally developed crime. Its assessment and punishment were determined even in times of Dracontius. It has been demonstrated that the punishment was transmitted into an independent area of the policy of polis. The purpose of punishment was to inflict suffering and torment on the offender and to intimidate him. The status of the offender was taken into account, as well as the degree of the committed actions. They also took into account the attitude of the offender to his act. Confession, repentance, or non-confession of a crime were taken into account, while determining the type of punishment. Non-confession of the crime entailed a more severe punishment. The attitude to prisoners of war, the specifics and types of their punishments have been considered. It has been concluded that the Ancient Hellas did not have a clear system of punishing servicemen. It is here, as in many other legal spheres, the lack of a clear understanding of the law was replaced by a moral and legal assessment. However, in Ancient Rome, unlike Ancient Greece, there was a clearer classification of war crimes and punishments, which was aimed at establishing a strict discipline in the army. The peculiarity of military punishments was the fact that they were different for the same crimes. The punishments were more severe during the war than in the period of peaceful life.

Показано, что полисный тип государственности обуславливал формирование в каждом городе-государстве своей самостоятельной правовой системы. Выяснено, что общей унифицированной системы наказаний военных в Давней Греции не существовало. Однако афинское право было более развитым среди всех правовых систем полисов и влияло на формирование правовых институтов других античных городов-государств. Показано, как уголовное право Афин достаточно чётко определяло наказания военных за наиболее опасные и тяжкие по своим последствиям преступления. Рассмотрены также отношение к военнопленным, специфика и виды их наказаний. Показано также, что в Древнем Риме, в отличие от Древней Греции, сложилась более чёткая классификация военных преступлений и наказаний, нацеленная на установление жёсткой дисциплины в армии.
Наказания военных в античных государствах
Punishment of servicemen in ancient states
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Давня Греція; поліс; міліційна армія; Давній Рим; військовозобов’язаний; покарання; злочин; система покарань; смертна кара; штраф; громадянин; військова служба; Ancient Greece; polis; militia army; Ancient Rome; liable for military service; punishment; crimes; punishment system; death penalty; fine; citizen; military service; Древняя Греция; полис; милиционная армия; Древний Рим; военнообязанный; наказание; преступление; система наказаний; смертная казнь; гражданин; военная служба